Orofacial Muscle Weakening in Facioscapulohumeral Muscular Dystrophy (FSHD) Patients - Dimitrios Konstantonis; Kyriaki Kekou; Petros Papaefthymiou; Heleni Vastardis; Nikoleta Konstantoni; Maria Athanasiou; Maria Svingou; Anastasia Margariti; Angeliki Panousopoulou (MDPI AG, 2022)
Background: Facioscapulohumeral muscular dystrophy is the third most commonly found type of muscular dystrophy. The aim of this study was to correlate the D4Z4 repeat array fragment size to the orofacial muscle weakening exhibited in a group of patients with a genetically supported diagnosis of FSHD. Methods: Molecular genetic analysis was performed for 52 patients (27 female and 25 male) from a group that consisted of 36 patients with autosomal dominant pedigrees and 16 patients with either sporadic or unknown family status. The patients were tested with the southern blotting technique, using EcoRI/Avrll double digestion, and fragments were detected by a p13E-11 telomeric probe. Spearman's correlation was used to compare the fragment size with the degree of muscle weakening found in the forehead, periocular and perioral muscles. Results: A positive non-significant correlation between the DNA fragment size and severity of muscle weakness was found for the forehead (r = 0.27; p = 0187), the periocular (r = 0.24; p = 0.232) and the left and right perioral (r = 0.29; p = 0.122), (r = 0.32; p = 0.085) muscles. Conclusions: Although FSHD patients exhibited a decrease in muscular activity related to the forehead, perioral, and periocular muscles the genotype-phenotype associations confirmed a weak to moderate non-significant correlation between repeat size and the severity of muscle weakness. Orofacial muscle weakening and its association with a D4Z4 contraction alone may not have the significance to serve as a prognostic biomarker, due to the weak to moderate association. Further studies with larger sample sizes are needed to determine the degree of genetic involvement in the facial growth in FSHD patients.